(untitled) (Revista Internacional de Formação de Professores, 2021)
The main objective of this work is to present some connections between Cognitive Neurosciences and teacher training. It is part of a postdoctoral. It is the result of theoretical research carried out in articles and books dated from 2008 to 2019. The results point to a need to present to future teachers and, already teachers, issues related to brain functioning in the act of learning, such as emotions, anxiety, gift, culture, brain plasticity and the transmission of information, among others. More collaborative research in this area is needed to consolidate the dialogue between Cognitive Neurosciences and Education.